Cardiovascular risk factors and variables associated in people aged 20-79 years in Manizales, Colombia - Vélez Alvarez, Consuelo; Gil Obando, Lida Maritza; Avila Rendón, Carmen Liliana; López López, Alexandra (Universidad y Salud, 2015)
Objective: To relate cardiovascular risk factors in people aged 20 to 79 years with sociodemographic, anthropometric and clinical variables and hard coronary risk category to 10 years in the city of Manizales. Materials and methods: A descriptive correlational study. Non-probability sampling. The sample were 405 people in the city of Manizales, who signed the consent and met inclusion criteria. Interviews, anthropometric and blood total cholesterol and HDL measurements were made. Results: There was statistically significant association p <0.05 and strength of high association (higher coefficient of 0.6) in the age with coronary risk according to blood pressure and antihypertensive treatment. The anthropometric variables were weight, body mass index with coronary risk as high blood pressure, total cholesterol, HDL cholesterol and abdominal obesity. The clinical variable was antihypertensive treatment with the risk factor of hypertension. Conclusions: There is predominance of modifiable anthropometric and clinical risk factors. Age and total cholesterol in the population surveyed represent greater risk by more than 50% of participants. Among the predisposing factors sedentary lifestyle was the most common. The category of hard coronary risk at 10 years was the most latent frequency.